Neonatal jaundice: Recommendations for follow-up and treatment - Emel Okulu (Elsevier, 2024)
Neonatal jaundice due to hyperbilirubinemia is a common and mostly a harmless problem. However, there is a risk of acute bilirubin encephalopathy and kernicterus, which are rare but can cause permanent neurological damage. In 2022, the American Academy of Pediatrics (AAP) updated its clinical practice guideline for neonatal hyperbilirubinemia in newborns who are at least 35 weeks gestational age. The 2022 AAP guideline incorporates updated phototherapy and exchange transfusion nomograms that feature higher bilirubin thresholds than previous guidelines, and includes risk assessments for escalation-of-care, which is a new definition, universal bilirubin screening procedures, and neurotoxicity risk factors that no longer consider race as a risk factor. It is necessary to exercise caution and consult with local experts when adapting the updated guideline in low- and middle-income countries due to potential lack of resources for screening, follow-up, and treatment.